IL‐1β and IL‐18: inflammatory markers or mediators of hypertension?. (December 2014) - Krishnan, S M; Sobey, C G; Latz, E; Mansell, A; Drummond, G R
<x xml:space="preserve">Abstract</x> Chronic inflammation in the kidneys and vascular wall is a major contributor to hypertension. However, the stimuli and cellular mechanisms responsible for such inflammatory responses remain poorly defined. Inflammasomes are crucial initiators of sterile inflammation in other diseases such as rheumatoid arthritis and gout. These pattern recognition receptors detect host‐derived danger‐associated molecular patterns (DAMPs), such as microcrystals and reactive oxygen species, and respond by inducing activation of caspase‐1. Caspase‐1 then processes the cytokines pro‐IL‐1β and pro‐IL‐18 into their active forms thus triggering inflammation. While IL‐1β and IL‐18 are known to be elevated in hypertensive patients, no studies have examined whether this occurs downstream of inflammasome activation or whether inhibition of inflammasome and/or IL‐1β/IL‐18 signalling prevents hypertension. In this review, we will discuss some known actions of IL‐1β and IL‐18 on leukocyte and vessel wall function that could potentially underlie a prohypertensive role for these cytokines. We will describe the major classes of inflammasome‐activating DAMPs and present evidence that at least some of these are elevated in the setting of hypertension. Finally, we will provide information on drugs that are currently used to inhibit inflammasome/IL‐1β/IL‐18 signalling and how these might ultimately be used as therapeutic agents for the clinical management of hypertension.